Physical activity is associated with improvements in other lifestyle behaviours - Hajat, Cother (BMJ Open Sport Exerc Med, 2019)
INTRODUCTION: We tested whether physical activity (PA) engagement is subsequently associated with additional health-promoting behaviours in a large-scale, real-world programme leveraging technology and behavioural science to reward healthy lifestyle behaviours. METHODS: In this observational, longitudinal study, we compared participants’ verified and self-reported health behaviours prior to and following their first verified engagement in PA recorded on the Vitality programme between 2014 and 2017. RESULTS: Of 34 061 participants, the mean duration in the programme was 40.1 (SD 12.6) months, and the median time until the first PA was 13.1 (SD 16.6) months, with a mean age of 42.0 (SD 11.1) years and 14 881 (43.7%) being male. Baseline weekly PA minutes were mean 62.8 (SD 129.7), 98 (SD 26.0) and 282.9 (SD 230.0) for the low, moderate and high groups, respectively. In the 12 months following the first PA, the low group increased weekly active minutes by 156% (40 (95% CI 28.6 to 51.0) to 102 (95% CI 94.5 to 109.8)); the moderate group increased weekly active minutes by 60% (85.0 (95% CI 76.4 to 93.5) to 136 (95% CI 130.2 to 141.8)); and no change was seen for the high group. Overall, individuals exhibited an increase of 26% in their weekly active minutes from an average of 130 min (95% CI 121.2 to 139.4) to 164 min (95% CI 157.5 to 169.8). Overall, fruit and vegetable daily servings increased from 2.7 (95% CI 2.6 to 2.8) to 2.9 (95% CI 2.9 to 3.0); Kessler Stress Scores decreased from 17.4 (95% CI 17.2 to 17.6) to 17.0 (95% CI 16.9 to 17.1); sedentary hours decreased from 11.3 (95% CI 11.1 to 11.5) to 10.8 (95% CI 10.7 to 11.0); alcohol consumption decreased from 1.8 (95% CI 1.7 to 2.0) to 1.6 (95% CI 1.5 to 1.7) weekly units; sleep increased from 7.1 (95% CI 7.06 to 7.16) to 7.2 (95% CI 7.13 to 7.20) hours/night. CONCLUSIONS: PA was followed by other health-promoting behaviours. PA interventions should also evaluate the indirect impact on other health behaviours.